KECEMASAN IBU HAMIL DITINJAU DARI INTENSITAS MEMBACA AL-QUR’AN DAN KELOMPOK USIA - Untari, Meta Maya; Rohmah, Faridah Ainur (Universitas Ahmad Dahlan, 2016)
AbstractThis study examined how intensity of reading Qur’an related to maternal anxiety and the differences level of maternal anxiety among three different age groups using quantitative method.The reading Qur’an intensity scale and maternal anxiety scale were used to collect the data and it was analyzed using product moment analysis technique and ANOVA test through SPSS version16.0 for Windows. Findings showed that generating r value of -0.826, p = 0.000 (p <0.01) which means that there was a highly significant negative relationshipbetween the intensity of reading the Qur’an and maternal anxiety. Analysis of variance resulted in a total value of df=39, F=11.788, p= 0.000( p <0.01) which means that there was highly significant difference level of maternal anxiety among age groups. The age group of pregnant mother below 20 years had average score of maternal anxiety for 50,58 while the age group of pregnant mother between 25-35 years reached about 37,75 and the oldestgroup one which was consist of pregnant mother over 35 years gained 39,33. Based on the result, it could be conclude the higher intensity of reading Qur’an, the lower maternal anxiety and vice versa. Moreover, there was a difference level of maternal anxiety among the age groups. The youngest age group had the lowest maternal anxiety level compare to the two other groups.Keywords:anxiety, maternal anxiety, intensity of reading Qoran,